PENGARUH PEMBELAJARAN BERDIFERENSIASI BERBANTUAN MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV DI UPTD SD NEGERI 122345 PEMATANGSIANTAR - Damanik, Hanna Cintia; Anton Sitepu; Dyan Wulan Sari HS; Juliana; Jhonas Dongoran; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of differentiated learning assisted by animated video media on the mathematics learning outcomes of fourth-grade students at UPTD SD Negeri 122345 Pematangsiantar in the 2024/2025 Academic Year. This study uses an experimental method with a one group pretest-posttest design. The subjects of the study were 30 fourth-grade students. The instruments used included learning outcome tests, student response questionnaires, and documentation. Data collection was carried out through learning outcome tests and student participation questionnaires that had been tested for validity and reliability. The pretest results showed an average value of student learning outcomes of 50.00 with a low category, while the posttest results increased to 70.00 with a high category. The Pearson correlation test produced a coefficient of 0.984. The t-count value is much greater than the r-table value of 0.349 at a significance level of 5% with 30 students as respondents, this indicates a strong relationship between the use of differentiated learning assisted by animated video media and students' mathematics learning outcomes. In addition, the results of the hypothesis test using the t-test obtained a calculated t value ≥ t table, namely 3.683 ≥ 1.714, which shows that there is a significant influence between differentiated learning assisted by animated video media on students' mathematics learning outcomes.